Training on Domestic Waste Management and Use of Maggots (Black Soldier Fly (BSF) Larvae) for Alternative Animal Feeding for Farmer Groups - Meindrawan, Bayu; Nafisah, Ainun; Syaifudin, Rizal; Aini, Fazriati Shofa; Romadoni, Fathurrahman Bintang (MOVE: Journal of Community Service and Engagement, 2024)
This program aims to provide training to the Setia Kawan Farmers Group (Poktan) in Baros Village so that they can optimize organic waste and produce alternative feed from magot (BSF larvae). Poktan raises livestock but this is not accompanied by sufficient knowledge, especially regarding the types of feed ingredients that can be used to meet the daily nutritional needs of livestock. Through the production of animal feed from magot, it is hoped that this can be a solution for the sustainable escalation of the livestock economy. The program starts from the socialization, training and assistance stages in the process of maintaining BSF and its application as an alternative animal feed. Partners are directly involved at all stages, namely by providing the latest information, determining organic waste collection points and maggot cultivation sites. After training, members of farmer groups are generally able to differentiate between organic and inorganic waste and know the basic principles of using maggots as alternative animal feed.